Effect of Plyometric Exercise and Leg Muscle Endurance on the Agility and VO₂max of Badminton Athletes - Sigit Nugroho; Rezha Arzhan Hidayat; Amat Komari; Kukuh Wahyudin Pratama; Manil Karakauki; Syed Kamaruzaman Syed Ali (OVS LLC, 2022)
Study purpose. This study aimed to determine: (1) the difference in the effect of plyometric ladder drill and hurdle drill exercises on agility and VO2max, (2) the difference in the effect of badminton athletes' high and low leg muscle endurance on agility and VO2max, (3) interaction between plyometric ladder drill and hurdle drill exercises with high and low leg muscle endurance on agility and VO2max. Materials and methods. This research was an experimental study with a 2x2 factorial design. The study sample was badminton athletes, totaling 24 people who were randomly selected from a population of 45 people. The instrument to measure agility was the T Drill Test, and that to measure VO2max was the Multistage Fitness Test (MFT). The data analysis technique used was the two-way ANOVA at a significance level of 0.05. Results. The study findings are as follows: (1) there is a significant difference in the effect of ladder drill and hurdle drill exercises on the agility of badminton athletes, whereas ladder drill and hurdle drill exercises have an equally good effect on increasing VO2max; (2) there is a significant difference in effect of badminton athletes' high and low leg muscle endurance on agility and VO2max; (3) there is a significant interaction between ladder drill and hurdle drill exercises and high and low leg muscle endurance on agility, whereas both exercises are equally well used to provide VO2max improvement. Conclusions. Based on the results of the study and the results of the data analysis that was carried out, it was concluded that there is a significant difference in the effect of plyometric ladder drill and hurdle drill exercises on the agility of badminton athletes.